2002
DOI: 10.1182/blood-2002-03-0955
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of the von Willebrand factor and Flt-1 promoters in the endothelium of hypoxanthine phosphoribosyltransferase–targeted mice

Abstract: An important limitation of standard transgenic assays is that multiple copies of the transgene are inserted randomly into the mouse genome, resulting in line-to-line variation in expression. One way to control for these variables is to target a single copy of the transgene to a defined locus of the mouse genome by homologous recombination. In the present study, we have used such an approach to target the promoters of 2 different genes, namely von Willebrand factor (VWF) and Flt-1, to the hypoxanthine phosphori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 39 publications
0
36
0
Order By: Relevance
“…3), mechanisms independent of the chemokine might be involved. [31][32][33] LSEC enhanced the CXCL12-driven transmigration of all CD4 ϩ T cell subsets investigated and the CXCL9-dependent transmigration of cytokine-producing memory cells, whereas the chemotactic effects of CXCL16, CCL20, and CCL21 on CD4 ϩ T cells were not significantly altered under the given experimental conditions. Thus, LSEC seem to exert differential effects on certain chemokines.…”
Section: Discussionmentioning
confidence: 92%
“…3), mechanisms independent of the chemokine might be involved. [31][32][33] LSEC enhanced the CXCL12-driven transmigration of all CD4 ϩ T cell subsets investigated and the CXCL9-dependent transmigration of cytokine-producing memory cells, whereas the chemotactic effects of CXCL16, CCL20, and CCL21 on CD4 ϩ T cells were not significantly altered under the given experimental conditions. Thus, LSEC seem to exert differential effects on certain chemokines.…”
Section: Discussionmentioning
confidence: 92%
“…1 Subsequently, we reported that a 1-kb fragment of the human VEGFR1 promoter (between Ϫ748 and ϩ284) contains information for endothelial-restricted expression in transgenic mice. 2 In the latter study, a single copy of the VEGFR1 promoter was targeted to the Hprt locus, thus providing a means to control for the effects of copy number and integration site on expression. In the current study, we used an identical Hprt targeting strategy to evaluate the activity of the VEGFR1 promoter containing a point mutation of 1 of the 2 ETS motifs, the CRE site, or the EGR binding element.…”
Section: Introductionmentioning
confidence: 99%
“…eNOS is comparable in its cell specificity with common endothelial markers such as CD31/PECAM and von Willebrand factor. mRNAs known to be even more restricted to the vascular endothelium than eNOS are uncommon but include the endothelial growth factor receptor tyrosine kinases VEGF-R1 (Flt-1), VEGF-R2 (Flk-1/KDR), Tie-1, and Tie2/Tek (8). Elucidating the mechanisms involved in the endothelial cell-specific eNOS would provide valuable insight into the poorly understood basis for endothelium-specific gene regulation.…”
mentioning
confidence: 99%